1995
DOI: 10.1148/radiology.196.1.7784579
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral ligaments and shoulder capsular mechanism: evaluation with MR arthrography.

Abstract: Background The glenohumeral ligaments are the most important passive stabilizers of the shoulder. The superior (SGHL), middle (MGHL) and inferior (IGHL) glenohumeral ligaments are currently evaluated by shoulder arthroscopy. To avoid surgery as a diagnostic procedure, optimization of MR imaging parameters could help to detect lesions of the glenohumeral ligament complexes. Recognition of acute and chronic glenohumeral ligament pathologies is important for the preoperative evaluation of the unstable and/or trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 0 publications
4
57
0
2
Order By: Relevance
“…8 Amongst 33 patients in our study, superior, middle and inferior glenohumeral ligaments were identified in 12.1%, 24.2% and 6.1% patients while these were detected in 90.9%, 84.8% and 93.9 % patients on MR arthrography. This is in close approximation to the previous study [10] in which the superior, middle and inferior glenohumeral ligaments were identified on MR arthrograms in 85%, 85% and 91 % of the patients respectively. Palmer et al, [11] identified superior GHL in 98% of 48 patients with MR arthrography which is in close consensus with our study.…”
Section: Discussionsupporting
confidence: 90%
“…8 Amongst 33 patients in our study, superior, middle and inferior glenohumeral ligaments were identified in 12.1%, 24.2% and 6.1% patients while these were detected in 90.9%, 84.8% and 93.9 % patients on MR arthrography. This is in close approximation to the previous study [10] in which the superior, middle and inferior glenohumeral ligaments were identified on MR arthrograms in 85%, 85% and 91 % of the patients respectively. Palmer et al, [11] identified superior GHL in 98% of 48 patients with MR arthrography which is in close consensus with our study.…”
Section: Discussionsupporting
confidence: 90%
“…31,32 Most modern shoulder surgeons would obtain an MRI of the joint before attempting definitive surgical repair. A pre-operative assessment of the degree of glenoid bone loss is particularly useful.…”
Section: Investigationsmentioning
confidence: 99%
“…Therefore, joint capsule itself can be depicted as a low intensity band, when fluid is present in the joint (Horii et al 1997). Recently, the usefulness of MR arthrography, using Gd-DTPA solution for evaluation of the labral-ligamentous complex of the shoulder, has been reported (Palmer et al 1994, Chandnani et al 1995, but equivalent images can be obtained by using 10 mL physiological saline.…”
Section: Discussionmentioning
confidence: 99%